Tinjauan Yuridis Tentang Perlindungan Hukum TenagaKerja Terhadap Jaminan Kesehatan Melalui BpjsDi Pt Daya Sakti Unggul CorporindoKabupaten Pacitan - Anggriawan, Akbar Berdhi, Nuswardhani, S.H, S.U, Inayah, S.H. M.H (2016)
The purpose of this study is to investigate the process of implementation of the agreement, the rights and obligations, as well as legal liability if one of the parties made a mistake in perjanjianantara BPJS and PT Daya Sakti Unggul Corporindo in social security in health. This research includes normative legal research. Source of data used secondary data obtained from the study of literature. Data were analyzed using qualitative analysis. The results showed that: First, the process of implementation of the agreement between the administering body and PT. DSUC in implementing social security in the health sector is happening when companies enroll their employees become participants BPJS to approve and sign the forms provided by BPJS; Second, the rules of the social security health sector is Law No. 40 of 2004 on National Social Security System (Navigation) and Law No. 24 of 2011 on Social Security Agency and other supporting regulations. Rights BPJS participant is to benefit health services, while liabilities BPJS participants are paying dues. BPJS organizing body entitled to receive payments, while liabilities BPJS Administering Agency is to provide benefits to all participants in accordance with the Law on the National Social Security System; Thirdly, the legal responsibility if one of the parties made a mistake in following the implementation of social security in the health sector, it includes default. For example BPJS does not cover the cost of care workers in hospitals, putting workers in a class lower maintenance, and others. Participants BPJS and / or their family members can claim his rights by making a complaint report to the Social Security Agency (BPJS), remedy of settling disputes through mediation, legal action settlement of disputes through the Consumer Dispute Settlement Board (BPSK), and legal efforts dispute resolution court. Keywords: BPJS, the implementation of social security agreements in the field of health